2021
DOI: 10.1111/jcmm.16658
|View full text |Cite
|
Sign up to set email alerts
|

GLCCI1 reduces collagen deposition and airway hyper‐responsiveness in a mouse asthma model through binding with WD repeat domain 45B

Abstract: Asthma is a serious public health problem globally, and the major types of it include allergic asthma, non-allergic asthma, late-onset asthma, fixed airflow-related asthma and obesity-related asthma. In accordance with the data from the World Health Organization, about 235 million people are affected by asthma worldwide. 1 Asthma is a heterogeneous disorder caused by various factors, such as allergies and air pollution, and is closely associated with inflammation and airway constriction. 2,3 Currently, althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…reported that during the occurrence and development of asthma, GLCCI1 inhibited autophagy and promoted airway remodelling by inhibiting WDR45 expression, thus alleviating asthma [19] . Qiufen Xun et al reported that GLCCI1 inhibits airway remodelling and ameliorates asthma by inhibiting the IL-13/periostin/TGF-β1 pathway [16] .…”
Section: Discussionmentioning
confidence: 99%
“…reported that during the occurrence and development of asthma, GLCCI1 inhibited autophagy and promoted airway remodelling by inhibiting WDR45 expression, thus alleviating asthma [19] . Qiufen Xun et al reported that GLCCI1 inhibits airway remodelling and ameliorates asthma by inhibiting the IL-13/periostin/TGF-β1 pathway [16] .…”
Section: Discussionmentioning
confidence: 99%
“…It can reduce collagen deposition and airway hyper-responsiveness in a mouse asthma model through binding with WD repeat domain 45B and represses airway remodeling of the asthmatic mouse via inhibiting IL-13/periostin/ TGF-β1 signaling. In addition, the reduced methylation level of the GLCCI1 gene body in peripheral blood influences PI3k-Akt and MAPK pathways and it may be contributed to detect asthma and asthma severity, 16,28,29 which may further strengthen the understanding of the role and mechanism of GLCCI1 contributed to the pathogenesis of AR.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, GLCCI1 promotes the binding between glucocorticoid receptor (GR) and GR-interacting protein 1 (GRIP1) but inhibits the recruitment of GRIP1 to interferon regulatory factors IRF1 and IRF3 ( Hu et al, 2021 ). In a mouse model of asthma GLCCI1 was shown to play a role in airway remodeling by modulating inflammatory signaling ( Xun et al, 2021a ; Xun et al, 2021b ). Interestingly, analysis of morbidity across the lifespan found a decreased risk of asthma in Down syndrome patients compared to general population or patients with other forms of intellectual disability ( Baksh et al, 2023 ).…”
Section: Understanding the Function And Regulation Of Dyrk1a Through ...mentioning
confidence: 99%